El Salvador : Technical Assistance Report-Monthly Volume Indicator of Economic Activity and Institutional Sector Accounts Mission. (IMF Staff Country Reports; Country Report ;, 2020)
A Technical Assistance (TA) mission was conducted by the Regional Technical Assistance Center for Central America, Panama, and the Dominican Republic (CAPTAC-DR) from February 26-March 2, 2018, to assist the Central Reserve Bank of El Salvador (BCRES) with concluding the compilation of the Monthly Volume Indicator of Economic Activity (indice Mensual de Volumen de la Actividad Economica - IMVAE)1 for dissemination and the development of annual institutional sector accounts (AISAs). The purpose of this mission was to follow up on the recommendations made by a previous mission that took place in September 2017: to compile the IMVAE with base year 2005, and to assess the data sources available for AISA compilation, using the data previously compiled for 2005 as background. The mission considered the BCRES decision to start regular compilation as of 2014.